Late Aptian (Early Cretaceous) dry-wet cycles and their effects on vegetation in the South Atlantic: palynological evidence - Carvalho, Marcelo de Araujo; Bengtson, Peter; Lana, Cecília Cunha; Sá, Natália de Paula; Santiago, Gustavo; Giannerini, Michele Cardoso da Silva (Cretaceous research, 2019)
The Cretaceous is generally conceived as one of the warmest geological periods in Earth history. The link between climate and plant distribution is here highlighted on the basis of palynological analyses. An upper Aptian well section from the Sergipe Basin in northeastern Brazil documents four cycles of dry–wet oscillations, based on palynological evidence. The cycles show a general trend of acceleration of the hydrological cycle. Dry periods are recorded mainly at the base of the section, with changes to more humid periods upwards. The dry periods are characterized by high to very high abundance of Classopollis classoides pollen grains. Already in the wet periods a conspicuous change in vegetation is recorded, with an increase in fern spores and upland flora, in particular Araucariacites australis pollen grains. The replacement of Classopollis by Araucariacites and ferns reflects a change from dry to wet conditions. The first dry–wet cycle (DWC-1) is recorded in the dominantly non-marine phase. At the base of this first cycle, intensive growth of anhydrite nodules is recorded. However, in beds overlying the evaporites, there is a conspicuous increase in flora associated with humid conditions (ferns and upland flora). DWC-2 starts with a pronounced peak of dinoflagellate cysts, which decrease abruptly accompanied by an increase in xerophytic flora (e.g., Classopollis classoides, Equisetosporites spp.). The abundance of xerophytic flora decreases upwards to give room for high abundances of fern spores, upland flora (e.g., Araucariacites australis, Cicatricosisporites spp.) and, in particular, dinoflagellate cysts. DWC-3 starts with a short interval containing a moderate abundance of xerophytes and a conspicuous wet flora and marine elements. With rising humidity, fern spore diversity also increased, suggesting that humidity was an important factor for the increase in diversity of this group. DWC-4 records minor peaks of xerophytic flora and a dominance of fern spores and upland flora. The progressive change in flora may be the result of displacement of the Intertropical Convergence Zone (ITCZ) and a relative sea-level rise.